Efficient synthesis of (3E)-3-(amino(aryl)methylidene)chromane-2,4-diones (=(3E)-3-(amino(aryl)methylene)-2H-1-benzopyran-2,4(3H)-diones) via a three-component reaction - Ghabraie, Elmira; Bararjanian, Morteza; Balalaie, Saeed; Rominger, Frank; Bijanzadeh, Hamid Reza (Helvetica chimica acta, 2011)
The Michael-type addition of a 4-hydroxycoumarin (=4-hydroxy-2H-1-benzopyran-2-one) 1 to a β-nitrostyrene (=(2-nitroethenyl)benzene) 2 in the presence of AcONH4 leads to substituted (3E)-3-[amino(aryl)methylidene]chroman-2,4-diones (=(3E)-3-[amino(aryl)methylene]-2H-1-benzopyran-2,4(3H)-diones) 4 (Table 1). High yields, short reaction time, and easy workup are advantages of this novel one-pot three-component reaction.